FORMATION OF SOCIAL AND PEDAGOGICAL COMPETENCE OF FUTURE TEACHERS (Web of Teachers: Inderscience Research, 2024)
The article reveals the content of the concept of "socio-pedagogical competence" and examines the principles of professional training of future teachers through the prism of the formation of socio-pedagogical competence.